Exploring Collaborative Care Effects on the Mental and Physical Health of Patients With and Without Violent Victimization Histories - Hullenaar, Keith L. (Journal of interpersonal violence, 2023)
Collaborative care is a multicomponent intervention delivered by frontline social work, nursing, and physician providers to address patients’ physical, emotional, and social needs. We argued that collaborative care may particularly benefit patients with a violent victimization history because it practices three principles of trauma-informed care: patient–provider collaboration, preventing repeat trauma in clinical and community settings, and delivering comprehensive mental and physical healthcare. We conducted an exploratory secondary data analysis of a collaborative care randomized clinical trial involving patients who presented with traumatic physical injury at a Level I trauma center in Washington state between 2006 and 2009. We used random-effect linear regression models to estimate how histories of multiple violent traumas moderated the effects of the collaborative care intervention on Short Form-36 Mental Component Summary (MCS) and Physical Component Summary (PCS) T-scores over time. Collaborative care significantly improved follow-up MCS scores among patients who experienced three to four types of violent victimization in their lifetime. Additionally, intervention effects on MCS scores at the 3- and 6-month follow-up were clinically stronger for patients who reported three to four types of violent victimization (3-month = 7.5, 95% confidence level [CI] = 5.1 to 18.7; 6-month = 11.9, 95% CI = 5.1 to 18.7) than those without a history of violent victimization (3-month = 0.8, 95% CI = −5.1, 6.6; 6-month = 5.6, −2.4 to 13.5). We did not find that intervention effects on PCS scores differed between these groups at any wave. Collaborative care may be a promising approach to delivering trauma-informed mental healthcare to patients with histories of multiple types of violent victimization.